Clinical picture of experimental crotalic poisoning in cattle (Crotalus durissus terrificus - positive crotamine) - Lago, Luiz Alberto do; Ferreira, Paulo Marcos; Facury Filho, Elias Jorge; Melo, Marilia Martins; Alzamora Filho, Fernando (Brazilian Journal of Veterinary Research and Animal Science, 2000)
With the aim of describing the clinical picture of experimental crotalic poisoning in cattle, five crossbred female, from two to three years old, were inoculated with type crotalic positive crotamine poison. The dosage was 0.03 mg/kg of body weight. The animals showed chronologically, the following clinical picture: at second hour of evaluation apathy, low head, deep lethargy and discreet swelling at the inoculation place; at sixth hour, local oedema had disappeared and myoclonia was observed in great muscle masses; at tenth hour, there was decreasing of muscular tonus, as well as superficial reflexes, motor incoordination appearing and esternal recumbency; at fourteenth hour it was observed pedal movement and loss of deep sensibility; at sixteenth hour, hind limbs flaccid paralysis and after twenty hours after poisoning it was observed dyspnea, salivation and death of all animals. Rectal temperature did not alter until the twentieth hour, however, from this time it decreased constantly until the death. The respiratory frequency kept within normal range for cattle, despite dyspnea observed since twentieth hour. Clinical course duration was 28 ± 9 hours and, even though these clinical alterations are common to other diseases, it can be judged that the speed and order of appearing are determinant factors in differential diagnosis.